Micellization properties of quinolinium based surfactants: 1-alkylquinolinium bromide and 6-hydroxy-1-alkylquinolinium-bromide by fluorimetry, conductivity and surface tension measurements and its parameters - Jyotsna Lakra; Deepti Tikariha Jangde; Birendra Kumar; Kallol K. Ghosh (Chemical Thermodynamics and Thermal Analysis, 2022)
Quinolinium surfactants possessing pyridinium rings have a wide range of biological applications due to its antimicrobial activity. In this study, we have used quinolinium based surfactant series i.e.1-alkylquinolinium bromide and 6-hydroxy-1-alkylquinolinium-bromide. The physicochemical behavior of quinolinium based surfactant have been carried out by various techniques viz. conductivity, surface tension and fluorescence measurements in aqueous and 10% (v/v) methanol at 300K.The critical micelle concentration (CMC) values found from conductivity, surface tension and fluorescence are in good agreement of a surfactant in aqueous and 10% (v/v) methanol. The CMC value of 1-alkyquinolinium-bromide series is higher than its derivative series (6-hydroxy-1-alkyquinolinium-bromide). The values of Гmax increases with increases chain length of the both the quinolinium surfactants, as well as Amin values increases with increasing chain length of surfactants.